Antibiotic susceptibility patterns of Escherichia coli isolates from patients with significant bacteriuria - Al- Mayahi, Firas Srhan Abd; Almohana, Ali Muhsin (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of this study was to the isolation and identification of E. coli bacteria from patients with significant bacteriuria and Antibiotic susceptibility patterns. During the period from March 2011 to May 2012, a total of 2000 urine samples were collected from patients with suspected UTI. Isolates were identified by traditional biochemical tests, and then confirmed by VITEK 2 system. 455 (22.8%) samples were recognized as significant bacteriuria. The study documented that E. coli is the most important uropathogen causing UTI and recovered from 207 (45.5%) patients. However, of the patients with significant bacteriuria, a total of 143 (31.4%) positive urine cultures were implicated in nosocomial infections. Additionally, 312 (68.6%) positive urine cultures were implicated in community-acquired infections. According to demographic data, it was observed that the number of patients with significant bacteriuria was higher in females, 309 (67.9%) compared to males, 146 (32.1%). The mean age of these patients was 39.1 years range from 2-90 years (standard deviation, 18.1years). Majority of patients with significant bacteriuria (269, 59.1%) were in the age group 20-50 years. Sensitivity of all isolates was tested against 23 Antibiotics. Results showed all isolates of E. coli were resistant 100% to ampicillin but sensitive100% to imipenem, the antibiotics resistance rate among the tested E. coli isolates ranged from 92.7%-74.9%, 69.6%-31.4% and 48.3%-10.2%, present to cephalosporins, fluoroquinolone and aminoglycosides respectively.